Charles H. Houston: An Interdisciplinary Study of Civil Rights Leadership - Conyers, James L. (Lexington Books, 2012)
This study seeks to examine the life and work of Charles Hamilton Houston and the scope of this project will focus on the implementation and organization of the proposed plan in three ways: philosophical ideas, constructive engagement, and lasting contributions of this legal scholar activist. When compiling scholarly articles for this volume, the challenge was examining not just legal precedents of Houston, but his contributions to the study of civic engagement, with emphasis on privilege, racism, disparity, and educational philosophy.